Yokohama : - Yonemura, Ann (Smithsonian Institution Press, 1990)
Following its opening to trade with America and Europe in 1859 (after more than two centuries of Japanese isolation), foreigners from the five treaty nations the US, Great Britain, France, Russia, and the Netherlands filled Yokahama, transforming the rural fishing village into a bustling international port. These extraordinary, colorful woodblock prints capture the excitement the harbor, the foreign peoples, and the technological wonders (from sewing machines to locomotives) that were introduced into Japan. Yonemura explores the prints in the context of the historical events that propelled Japan into the modern age.